2020
DOI: 10.1088/1361-6595/ab5eca
|View full text |Cite
|
Sign up to set email alerts
|

Implications of thermo-chemical instability on the contracted modes in CO2 microwave plasmas

Abstract: Understanding and control over plasma instabilities and contraction phenomena in reactive flows is essential to optimize the discharge parameters for plasma processing applications such as fuel reforming and gas conversion. In this work, we describe the characteristic discharge modes in a CO 2 microwave plasma and assess the impact of wave coupling and thermal reactivity on the contraction dynamics. The plasma shape and gas temperature are obtained from the emission profile and the Doppler broadening of the 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(113 citation statements)
references
References 46 publications
(118 reference statements)
16
95
0
Order By: Relevance
“…It was indeed demonstrated, both experimentally (e.g., van Rooij et al, 2015;Bongers et al, 2017;den Harder et al, 2017;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020 and computationally (e.g., Berthelot and Bogaerts, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019), that in practice, the vibrational non-equilibrium is not the leading mechanism in (sub)atmospheric MW or GA CO 2 plasmas, and that the CO 2 conversion is thermal, although Pietanza et al (2020) suggested to act with caution on this assumption, as their model still showed clear deviations from equilibrium, even at temperatures of 3,500-5,500 K.…”
Section: Improving the Energy Efficiencymentioning
confidence: 74%
See 4 more Smart Citations
“…It was indeed demonstrated, both experimentally (e.g., van Rooij et al, 2015;Bongers et al, 2017;den Harder et al, 2017;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020 and computationally (e.g., Berthelot and Bogaerts, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019), that in practice, the vibrational non-equilibrium is not the leading mechanism in (sub)atmospheric MW or GA CO 2 plasmas, and that the CO 2 conversion is thermal, although Pietanza et al (2020) suggested to act with caution on this assumption, as their model still showed clear deviations from equilibrium, even at temperatures of 3,500-5,500 K.…”
Section: Improving the Energy Efficiencymentioning
confidence: 74%
“…In MW and GA plasmas, the electron temperature is still higher than the gas temperature (hence, they are not really thermal plasmas), but the vibrational and gas temperature are often close to each other (i.e., VT equilibrium), so they can also be considered as quasi-thermal plasmas. For this reason, the CO 2 conversion proceeds mainly by thermal reactions in MW and GA plasmas at practical operating conditions (van Rooij et al, 2015;Berthelot and Bogaerts, 2017;Bongers et al, 2017;den Harder et al, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020.…”
Section: Different Dissociation Mechanisms In Different Plasma Typesmentioning
confidence: 99%
See 3 more Smart Citations